DETERMINANTS OF COMMUNICATIVE SKILLS IN STUDENTS WITH MILD INTELLECTUAL DISABILITIES - Kriuchko, Natalia (Sworld-Us Conference proceedings, 2023)
Тhe purpose of this article is to identify and characterize the determinants of communicative skills development in elementary school students with mild intellectual disabilities. The determinants include consideration of individual psychophysical develop